POTENSI BIOTOKSIKAN EKSTRAK ETANOLIK KULIT BIJI METE (Anacardium occidentale L.) PADA SISTEM REPRODUKSI JANTAN TIKUS PUTIH (Rattus norvegicus Berkenhout 1769) GALUR WISTAR - , Herlina Menufandu ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Effects of phenolic compounds in ethanolic extract of cashew nut shell (Anacardium occidentale L.) on the reproductive system of male Wistar rats (Rattus norvegicus Berkenhout 1769) was investigated. Conducting research with CRD experiment, using 12 male Wistar rats aged 6 weeks old, were divided into four treatment groups with three replications. The control was group I